Avaliação da palatabilidade de soluções de NaCl e NaHCO3 em ratos Wistar durante o desenvolvimento da hipertensão 2-rins-1-clipe - Pereira, Maxwel Sampaio (2023)
The renin-angiotensin-aldosterone (SRAA) modulates sodium intake. Repeated episodes of extracellular dehydration sensitize RAAS and stimulate sodium appetite. Hypertensive 2-kidney-1-clip (2K1C) rats show chronic RAAS activation and high NaCl intake induced by central angiotensin II injection. It is possible that 2K1C rats also present sensitization of the natriorexigenic response induced by hypovolemia associated to body sodium depletion. The aim of this study was to evaluate the mineral preference and palatability of 2K1C rats for different concentrations of NaCl and NaHCO3, in addition to the possible sensitivity to the sodium depletion protocol. Male Wistar rats (150 - 190 g) were initially submitted to unilateral renal stenosis by surgical insertion of a silver clip (0.2 mm opening) or Sham surgery. In Experiments 1 and 2, between the 4th-5th, 8th-9th and 12th-13th postoperative week (PW), the rats were kept in individual metabolic cages with rodent chow, a bottle containing drinking water and another containing NaCl or NaHCO3 at concentrations of 0; 0.08; 0.15; 0.23 or 0.3 M, for 3 days each concentration. The averaged daily intake of the last 2 days was calculated. In Experiment 3, during the 3rd, 7th and 11th PW the rats were housed in metabolic cages for six days with water, NaCl 0.23 M, chow and low sodium food. On the 7th day, the animals were submitted to s.c. injections of furosemide (1 ml/rat) associated with low sodium diet for 24 h. After the period, two bottles were offered to the animals, one containing water and another NaCl 0.23 M for a period of 180 minutes. At the end, the mean arterial blood pressure (MAP) and heart rate (HR) were measured, subsequently the animals were euthanized. The rats submitted to clip insertion were subsequently subdivided into hypertensive group (2K1C-H), with MAP > 129 mmHg, and normotensive group (2K1C-N), with MAP < 130 mmHg. Only between the 4th and 5th PW, the intake of NaCl 0.23 M by the 2K1C-H group (14 ± 3 ml/100 g bw/24 h) was significantly higher than 2K1C-N (5 ± 2 ml/100 g bw/24 h) and Sham (4 ± 2 ml/100 g bw/24 h, p<0.05). The NaHCO3 intake was similar between the groups during the weeks of hydromineral intake records. The NaCl 0.23 M intake of rats 2K1C-H (38.9 ± 10.7 ml) was significantly higher than 2K1C-N (21.0 ± 2.1 ml) and Sham (17.0 ± 3.2 ml, p<0.05) in the 12th PW. The results suggest that normohydrated 2K1C-H rats present a specific preference curve to NaCl in "inverted U" with increased palatability to NaCl 0.23 M, considering there was no preference for any NaHCO3 concentration offered. In addition to sensitization to sodium appetite induced by furosemide protocol.